The Effect of Aromatherapy Lavender Essential Oils on the Quality of Life of Patients with Chronic Diseases and Pain - Aldi, Danya Rania; Algristian, Hafid (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2025)
This study aims to examine the therapeutic benefits of lavender essential oil (LEO) on pain management and its potential to improve the quality of life in patients with chronic diseases. Chronic pain is a common and incapacitating illness that profoundly affects physical and mental health, leading to increased interest in complementary and alternative therapy. Lavender essential oil, recognized for its soothing aroma and therapeutic benefits, has garnered interest for its analgesic, anxiolytic, and anti-inflammatory characteristics. These advantages are thought to be facilitated by several physiological processes, including the regulation of transient receptor potential (TRP) channels, which are involved in sensory perception and pain signalling. This study utilizes a systematic literature review technique, concentrating on both clinical and experimental studies to investigate the effectiveness of lavender essential oil in alleviating pain. The analysis includes many chronic illnesses such as neuropathic pain, arthritis, cancer-related pain, and fibromyalgia. The studies incorporated in the review investigate several administration modalities, including inhalation, topical application, and aromatherapy massage. Inhalation has consistently been linked to decreased pain perception, enhanced respiratory patterns, and increased mental well-being, underscoring the many advantages of lavender essential oil in holistic care environments.